Effectiveness of Three Types of Moisturizers on Senile Dry Skin: A Randomized Controlled Pilot Trial - Miku Aoki; Natsuki Hata; Junko Yotsuya (Hindawi Limited, 2023)
Background. For dry skin, the application of a hypoallergenic moisturizer twice daily is recommended in elderly individuals. However, it is not known which is the most effective and appropriate moisturizer among the commercially available moisturizers. Aims. In this study, we aimed to investigate the efficacy of the three widely used moisturizers for the treatment of senile dry skin. Patients/Methods. This interventional study involved elderly individuals aged >65 years who were living in a nursing home. The participants were randomly divided into the interventional (moisturizers A, B, and C) and conventional care groups. Moisturizers A, B, and C were applied on the skin of each member of the three intervention groups twice daily for 8 weeks. The water content of the stratum corneum and transepidermal water loss (TEWL) were evaluated before and after the intervention. Changes in these parameters among the groups were compared using two-way analysis of variance and a posthoc test. Results. Moisturizers A, B, and C and conventional care groups comprised six, seven, five, and four participants, respectively. The water content of the stratum corneum was significantly higher in the moisturizer A p=0.01 and B p=0.047 groups than in the conventional care group. There was no significant difference in TEWL among the groups. Conclusions. In terms of the appearance of the skin, white powder and small scales were both reduced in group A. Taken together with the water content, this was considered a clinically significant change.